Teaching Health and Physical Education to Deaf Students: Reviewing the Challenges and Solutions - Shankar Prasad Acharya, (HPE Forum, 2026)
This study examines the challenges and solutions in teaching health and physical education (HPEd) to deaf students. Despite the importance of HPEd for physical, cognitive, and social development, deaf learners face multiple barriers due to communication difficulties, inappropriate curriculum, and inadequate instructional resources. The main objective of the study was: to identify the major challenges to teach HPEd for the deaf students, and to explore possible solutions to address the challenges. A descriptive research design was adopted, where primary data were collected from 36 students of grades 11 and 12 through census sampling, and one HPEd teacher was selected using purposive sampling at Bahira Bal Ma. Vi., Siddharthanagar, Rupandehi. Data were analyzed using simple statistical tool; mean and percentage. The results showed that 94.44% of students considered the curriculum unsuitable for their level, 72.22% found teaching methods ineffective, and 72% reported insufficient teaching aids. Communication barriers were evident, with both teachers and students possessing only moderate sign language proficiency. Furthermore, the evaluation system, mainly based on written and practical examinations which is used for general students, did not adequately reflect deaf students’ real achievements. In conclusion, the study highlights the urgent need for a deaf-friendly curriculum, activity-based pedagogy, greater use of visual and interactive teaching aids, professional training for teachers in sign language and inclusive practices, and assessment reforms emphasizing practical performance. Implementing these solutions can significantly enhance deaf students’ access to and participation in HPEd, thereby promoting inclusive and equitable education in practice.